Unveiling the rarity: a laryngeal myxoma arising from the epiglottis - Vayalakath, Jishna; Madayambath, Sagesh; Kizhakkayil Meethal, Surendran; Kannichankandi, Hitha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Myxomas are benign mesenchymal neoplasms which are rare in the head and neck region. Here, we present a case of a myxoma arising from the epiglottis, an exceedingly rare location in the head and neck. Our patient presented with a solid lesion arising from the lingual surface of the epiglottis. Histopathological examination and immunohistochemistry confirmed the diagnosis of myxoma. A myxoma arising from the epiglottis has not been reported in the literature during the last three decades. Myxomas should be considered in the differential diagnosis of benign-looking lesions of the larynx. The slow-growing nature of the tumor often delays symptom onset and diagnosis. Although recurrence is rarely reported in laryngeal myxomas, close follow-up is recommended.